Study on a Single-Component Solvent-Free Polyurethane Adhesive Prepared with Latent Curing Agent - Hu, Xiao-Yong; Chen, Yao; Han, Jian-Xiang; Chen, Jing-Fan (Asian Journal of Chemistry, 2013)
A novel single-component solvent-free polyurethane adhesive is prepared by using a environmental latent curing agent. As the reaction between free isocyanate groups and H2O replaced by latent curing agent and H2O, the release of CO2 during intermediate steps is avoided. Constantly, there is no foam in film. The performance of adhesive is improved due to the bifunctional structure of latent curing agent.